Pendidikan Sepanjang Hayat sebagai Pilar Pembangunan Berkelanjutan: Peluang dan Tantangan - Isval Maulana; Nur Khasanah (Yayasan Al-Afif, 2025)
Lifelong learning is a fundamental concept that positions learning as an integral part of human life at every stage of development. In the context of sustainable development, lifelong education serves as a crucial pillar in fostering an adaptive, innovative, and competitive society amid rapid global changes. Through continuous education, individuals are expected to develop competencies, values, and attitudes that support the balance between economic, social, and environmental dimensions. However, the implementation of lifelong learning in Indonesia still faces several challenges, including unequal access to education, limited infrastructure, low digital literacy, and the lack of optimal collaboration among government, educational institutions, and society. On the other hand, the advancement of digital technology and open education policies present significant opportunities to expand access and improve the quality of learning. Therefore, a comprehensive strategy integrating formal, non-formal, and informal education is essential to realize lifelong learning as a foundational pillar of sustainable development.